WTAP ‐mediated m6A RNA methylation promotes diabetic foot ulcer healing under negative pressure wound therapy - Yutong Li; Wenhua Chen; Jianhao Lu; Xiaoyue Lin; Ying Tang; Jiaxu Li; Mingwei Chen (Journal of Diabetes Investigation, 2026)
ABSTRACT Aims To investigate the role of RNA N6‐methyladenosine (m6A) methyltransferase Wilms tumor 1‐associated protein (WTAP) in negative pressure wound therapy (NPWT) for diabetic foot ulcers (DFU). Materials and Methods We enrolled 46 DFU patients and 16 non‐diabetic chronic ulcer patients treated with NPWT. Total m6A levels and the expression of methyltransferases (METTL3, METTL14, and WTAP) in wound margin tissues were measured before and after NPWT. High glucose‐induced HaCaT and HDF cell models, alongside an in vitro negative pressure system, were used to evaluate the effect of negative pressure on WTAP expression and the impact of WTAP alteration on cellular functions. Results Before NPWT, METTL3, METTL14, WTAP and m6A levels were significantly lower in DFU patients than in the non‐diabetic chronic ulcer patients. After one week of NPWT, these parameters increased significantly in both groups, and a positive correlation was observed between WTAP and m6A levels. Notably, the increase in WTAP expression exhibited a significant positive correlation with the 4‐week healing outcome in DFU patients. In vitro, negative pressure significantly reversed the high glucose‐induced WTAP downregulation in both HaCaT and HDF cells, while WTAP knockdown profoundly impaired their proliferation and migration. Conclusions NPWT is associated with improved DFU healing and the restoration of WTAP‐m6A levels, and its effect may be related to negative pressure promoting WTAP expression to enhance wound cell proliferation and migration.